Pengaruh Minum Air Kelapa Muda Hijau Terhadap Penurunan Nyeri Haid (Dismenorhea) Pada Siswi SMA PAB 5 Klumpang Kec. Hamparan Perak Kabupaten Deli Serdang Tahun 2018 - Elvi Era Liesmayani; Novalita Oriza; Santi Intan Sari (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
Background: Menstrual pain (dysmenorhea) is pain that is felt during menstruation. Pain during menstruation can be treated using herbal remedies, one of which is coconut water. In Indonesia, the incidence of dysmenorrhea is 64.25%, consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. The prevalence of dysmenorrhea in Indonesia states that dimenorhea is around 55% among productive age groups. This study aims to determine the effect of drinking green young coconut water on reducing menstrual pain (dysmenorhea). This research is a quantitative study using a pre-experimental design with a one group pre-post test approach. The sample for this study was SMA PAB 5 Klumpang students using the qouta sampling technique, namely 17 people. Data analysis used the Wilcoxon test. The results showed that there were differences in mean scores The average decrease in menstrual pain before and after being given green young coconut water is from 3.29 to 4.65. Wilcoxon test results obtained A-Symp Sig (2-tailed) value is p = 0.000 (<0.05). Conclusion: there is an effect of drinking green young coconut water on reducing pain. It is recommended that respondents increase their knowledge in dealing with menstrual pain using non-pharmacological drugs, for institutional recipients of information on the benefits of coconut water in reducing menstrual pain, and for future researchers to develop it further.